EFFECTIVENESS OF VAGINAL CONE THERAPY ON URINARY INCONTINENCE AMONG WOMEN IN SAVEETHA MEDICAL COLLEGE HOSPITAL, THANDALAM, CHENNAI - J, JAGADEESWARI; S, KALABARATHI; P, MANGALAGOWRI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The present aims to assess the level of urinary incontinence in experimental and control group, to assess the effectiveness of vaginal cone therapy on urinary incontinence in experimental group and control group and to associate the post-test level of urinary incontinence with the selected demographic variables among women in the experimental group. Methods: A quantitative quasi-experimental research design was conducted among 60 women with urinary incontinence. Convenience sampling technique was used. Semi-structured interview method was used to collect the demographical data and level of urinary incontinence among women was assessed by urinary incontinence diagnosis questionnaire. Results: Among 60 samples in experimental group 26 women had a moderate level of urinary incontinence, and 4 women had slight urinary incontinence whereas in control group 24 women had moderate level of urinary incontinence and 6 women had slight urinary incontinence. The study results show significant improvement in level of urinary incontinence among experimental group than the control group after the intervention at the level of p<0.05. This reveals that vaginal cone therapy is highly significant in the experimental group because pelvic muscle strength had improved and allows the patient to increase the physiological consciousness and promotes the muscle tone after the use of a vaginal cone. Conclusion: This study proves that vaginal cone therapy is the effective non-pharmacological method, cost-effective method and had no side effects which can be used to treat female urinary incontinence.